PKCδ reveals a tumor promoter function by promoting cell proliferation and migration in somatotropinomas - Lei, Zhuowei (Int J Clin Exp Pathol, 2018)
Protein kinase C δ (PKCδ), a subtype of PKC family, has been recognized as a tumor promoter or suppressor depending on different tissue specificities in various tumor types. However, the effects of PKCδ on somatotropinomas are poorly understood. This study aims to explore the precise role of PKCδ in promoting tumor progression in somatotropinomas. In the present study, we examined the expression levels of PKCδ in clinical specimens of human somatotropinomas to show that PKCδ overexpression correlated with invasive properties of somatotropinomas. Furthermore, we employed rat anterior pituitary GH3 cells as the experiment model to demonstrate that PKCδ activation by PKC agonist (Phorbol-12-myristate-13-acetate, PMA) significantly promoted the proliferation and migration potential of GH3 cells, and these effects could be abolished following PKCδ inhibition by specific inhibitor Rottlerin. Mechanistically, PKCδ activated ERK1/2 signaling, which was responsible for PKCδ-induced promotion of GH3 cell proliferation and migration. Taken together, our results indicated that PKCδ functions as a tumor promoter by promoting cell proliferation and migration in somatotropinomas.